2017
DOI: 10.1016/j.tranon.2016.10.004
|View full text |Cite|
|
Sign up to set email alerts
|

Up-Regulation of RFC3 Promotes Triple Negative Breast Cancer Metastasis and is Associated With Poor Prognosis Via EMT

Abstract: Triple-negative breast cancer (TNBC) was regarded as the most aggressive and mortal subtype of breast cancer (BC) since the molecular subtype system has been established. Abundant studies have revealed that epithelial-mesenchymal transition (EMT) played a pivotal role during breast cancer metastasis and progression, especially in TNBC. Herein, we showed that inhibition the expression of replication factor C subunit 3 (RFC3) significantly attenuated TNBC metastasis and progression, which was associated with EMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 33 publications
3
47
0
Order By: Relevance
“…Previous studies indicated that the overexpression of RFC3 promotes breast cancer metastasis and MCF-7 cell proliferation, and is associated with poor prognosis via the epithelial–mesenchymal transition, while the knockdown of RFC3 expression can inhibit MCF-7 cell proliferation and invasion. 19 , 20 Consistent with these conclusions, our findings showed that the downregulation of RFC3 levels with small interfering hsa_circ_0011946 resulted in the inhibition of migration and invasion in MCF-7 cells. Breast cancer patients with high RFC3 levels have a higher risk of distant metastases, 19 thus RFC3 might be an oncogene and might serve as a therapeutic target for breast cancer.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous studies indicated that the overexpression of RFC3 promotes breast cancer metastasis and MCF-7 cell proliferation, and is associated with poor prognosis via the epithelial–mesenchymal transition, while the knockdown of RFC3 expression can inhibit MCF-7 cell proliferation and invasion. 19 , 20 Consistent with these conclusions, our findings showed that the downregulation of RFC3 levels with small interfering hsa_circ_0011946 resulted in the inhibition of migration and invasion in MCF-7 cells. Breast cancer patients with high RFC3 levels have a higher risk of distant metastases, 19 thus RFC3 might be an oncogene and might serve as a therapeutic target for breast cancer.…”
Section: Discussionsupporting
confidence: 87%
“… 13 , 14 RFC subunit 3 (RFC3) is one of the small subunits on the RFC complex and was originally purified from HeLa cells and shown to be essential for the in vitro replication of Simian virus 40. 14 In recent years, the various roles of RFC3 have been increasingly illuminated in studies of malignancies, including hepatocellular carcinoma, 15 ovarian carcinoma, 16 esophageal adenocarcinoma, 17 colorectal cancer, 18 and breast cancer, 19 , 20 suggesting that RFC3 may be a potential oncogenic gene involved in tumorigenesis. However, it is not clear how RFC3 regulates the progression of breast cancer when combined with circRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, PCNA is a well‐established proliferation marker in some types of cancer . RFC3 is associated with proliferation activity of breast cancer cells or poor prognosis in ovarian cancer patients . Overexpression of FEN1 has been associated with enhanced cancer cell proliferation or poor clinical outcome in gastric, breast, ovarian and non‐small‐cell lung cancer .…”
Section: Discussionmentioning
confidence: 99%
“…The MCM complex forms the core of the DNA replicative helicase and, interestingly, is associated with cisplatin resistance [79]. Increased RFC expression has been shown to be associated with epithelialmesenchymal transition and poor outcomes in both lung and breast cancer [80]. Other complexes we identified, such as the BRCC and the Condesin complexes, have been linked to DNA repair in cancer [81,82].…”
Section: Discussionmentioning
confidence: 95%